ANALYSIS OF UBC UTILIZATION IN THE EXISTING COAL POWER STATION CASE STUDY : SURALAYA POWER STATION - Gandhi Kurnia Hudaya; BUKIN DAULAY; Iwan Rijwan (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2008)
Coal resources in Indonesia mostly (65 %) are categorized as LRC (Low Rank Coal). Currently, the Indonesian Government is encouraging to use LRC as the main source of energy in the national energy mixed policy, including the acceleration program of constructing 10,000 MW Power Plant. With the advanced technologies, such as Upgraded Brown Coal (UBC) process, LRC can be used optimally, particularly for the power plant. Suralaya Generation Business Unit (SGBU), which is the largest coal power plant in Indonesia, recently has to use lignite coal or low rank coal because the price of medium and high rank coal is too expensive. This paper conducted to identify the problems faced by SGBU in using lignite coal and to evaluate the benefit of UBC process if used in SGBU to be blended with lignite. From the evaluation, it can be concluded that UBC process will give benefit to SGBU by reducing ash pollution and give economic benefit of Rp 507 billion per year maximum.